Perbedaan Rerata Nilai Fev1 Pada Laki- Laki Antara Pekerja Kantoran Dan Pekerja Yang Terpapar Polusi - Lathifah, Annisa Nurul, dr. Sri Wahyu Basuki, M.Kes, dr. Dodik Nursanto (2015)
Air Pollution was one of problem happened in urban area. Air pollution was really related to lung function. Continued expose of air pollution could decrease of lung function especially on the FEV1 value that related to obstructive disorder. FEV1 was one of pulmonary function test that indices of lung growth. This research used analytic observational research design with cross sectional approach. This research was done on October to December 2014 in three different places such as Satlantas Surakarta, office of BAA and BAU in Campus I UMS and Biomedical I Laboratory Sub laboratory Physiology Medical Faculty UMS. Sample used in this research was officer and pollutant exposed workers such as Supeltas. Sample was divided into two groups, each group consisted 30 respondents. Sampling used in this research was purposive sampling. Independent T test on SPSS 17 for windows was used to analyze difference mean value of FEV1 in men between officer and pollutant exposed workers. This research showed that mean value of FEV1 in officer (2.8283) higher than pollutant exposed workers (1.9877). Independent T test result obtained the value of significancy 0.000 (p=0.000). It could be conclude that there was significant difference mean value of FEV1 in men between officer and pollutant exposed workers (p<0.05)